2009
DOI: 10.1002/chem.200801920
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding between an Isoindoline Nitroxide and 1,4‐Diiodotetrafluorobenzene: New Tools and Tectons for Self‐Assembling Organic Spin Systems

Abstract: Radical assembly: Halogen bonding has been observed for the first time between an isoindoline nitroxide and an iodoperfluorocarbon (see figure), which cocrystallize to form a discrete 2:1 supramolecular compound in which N--O(.)I halogen bonding is the dominant intermolecular interaction. This illustrates the potential use of halogen bonding and isoindoline nitroxide tectons for the assembly of organic spin systems.The isoindoline nitroxide 1,1,3,3-tetramethylisoindolin-2-yloxyl (TMIO) and 1,4-diiodotetrafluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 68 publications
6
81
1
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41] The NMR and other spectroscopic measurements of halogen bonds have also been reported. [29,[43][44][45][46][47][48] The electron density around the halogen atoms has been studied by ab initio molecular orbital calculations. [52][53][54][55][56][57][58][59] Symmetry-adapted perturbation theory (SAPT), atoms-in-molecules (AIM) and natural bond orbital (NBO) calculations were applied to elucidate the nature of halogen bonds.…”
mentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] The NMR and other spectroscopic measurements of halogen bonds have also been reported. [29,[43][44][45][46][47][48] The electron density around the halogen atoms has been studied by ab initio molecular orbital calculations. [52][53][54][55][56][57][58][59] Symmetry-adapted perturbation theory (SAPT), atoms-in-molecules (AIM) and natural bond orbital (NBO) calculations were applied to elucidate the nature of halogen bonds.…”
mentioning
confidence: 99%
“…15a) [59]. This work was extended by Micallef to isoindoline nitroxide [60,61]: a similar trimeric entity was crystallized (Fig. 15b) while EPR spectroscopy performed in solution with pentafluoroiodobenzene indicated that halogen bonding induces an increase in electron density at the nitroxide nitrogen nucleus and an increase in the nitroxide rotational correlation time.…”
Section: Nitronyl Radicalsmentioning
confidence: 92%
“…Optimizing the electrostatic and charge transfer aspects have been successfully used in designing of drugs, liquid crystals, organic semiconductors, magnetic materials, nonlinear optical materials, and templates for solid synthesis. [12][13][14][15][16] Conventionally, halogen bonds have been divided into two classes, TypeI and Type II (Fig. 3), based solely on the bonding geometry.…”
Section: Halogen Bonds (Xb)mentioning
confidence: 99%